(untitled) - Szczerkowska-Dobosz, Aneta; Rębała, Krzysztof; Lange, Magdalena; Sokołowska-Wojdyło, Małgorzata; Sobjanek, Michał (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2006)
Psoriatic arthritis is a genetically inherited disease with significant associations with human leukocyte antigens (HLA). Similarly to psoriasis vulgaris Cw6 antigen has been repeatedly indicated to be the most significant marker for risk prediction of psoriatic arthritis. The aim of the study was to compare the frequency of HLA-C locus alleles in patients with psoriatic arthritis and healthy controls in the same ethnic group in Poland and to correlate them with age of onset of psoriatic skin changes and joint symptoms. HLA-C locus alleles of forty-one patients and eighty controls were determined by a PCR low resolution method. The Cw*06 allele occurred more frequently (56% vs 18.7%; χ 2 =12.91; p=0.0003; pc=0.004, RR=5.54, OR=3.76) in patients with psoriatic arthritis than in controls. Patients who carried the HLA-Cw*06 allele had a significantly earlier mean age of onset of both psoriasis (21.4 years, p=0.01) and arthritis (25.7 years, p=0.008) compared with Cw*06-negative patients. Our results confirm the association between Cw*06 allele and psoriatic arthritis in the northern Poland population and suggest that the HLA-Cw*06 may determine not only disease susceptibility, but also the age of onset of psoriatic arthritis.